Integration and insight on information, communication and technology for sustainable education - Pandey, Shiv Ram; Belbase, Narayan; Boonroungrut , Chinun; Girija, V.; Tripathi , Yashodham; Pandey , Supriya (A Bi-annual South Asian Journal of Research & Innovation, 2026)
This review based article has articulated ideas on integration and insight on ICT for sustainable education. In the field of education, a noteworthy paradigm shift is taking place through the usage of Information and Communication Technology (ICT), which serves as a transformative tool to shift into the neo-technology of teaching and learning. ICT in education refers to the integration of Information and Communication Technologies, including hardware, software, and networks, to advance teaching and learning by providing digital tools, facilitating online communication, supporting e-learning, and personalizing educational experiences for learners. It broadens the horizon of Information Technology (IT) to encompass all communication forms, using digital resources to make learning more engaging, accessible, and efficient for both learners and educators. Most of the nations have effectively incorporated ICT in their educational systems, understanding its potential to develop student engagement, enhance critical thinking skills, and prepare learners for technological advantage. ICT provides insights into the current condition of teachers’ efficiency and technology use in teaching and recognizes pathways for further improvement in techno-based teaching and for promoting students’ advancement. ICT integration in educational sectors seems much required. However, it depends on teachers’ efficiency and the availability of required equipment. Teachers’ proficiency in using ICT tools immensely impacts the learners’ learning experiences and educational outcomes. The findings from the study will be beneficial not only to the policy framers but also to the teachers and researchers. Educational strategies influence integration of ICT to promote active students’ engagement, shifting their roles from passive listeners or observers to active participants in the learning process.